Karakterisasi Material Kemasan Pulp Cetak Tanpa Perekat Dari Pulp Batang Jagung - Muhammad Rifki Aulia Rahman; Warman Fatra; Zuchra Helwani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Molded pulp is an alternative packaging which has renewable and biodegradable properties. The use of molded pulp as packaging material still constrained due to the specific data that describes the characteristics of molded pulp has not widely publicized yet. This study was conducted to identify the characteristics of molded pulp as an alternative packaging material. Cornstalk was selected as raw materials which has abundant availabilty. Molded pulp packaging was manufactured by thermoformed methods. The thermoset nature of lignin in cornstalks would give possibilties in manufacture of molded pulp without using adhesive. The results showed the mechanical characteristics of binderless molded pulp from cornstalk pulp which have tensile index from 17.78 to 35.78 Nm/g, tear index from 9,25 to 26,09 mN.m2/g, and burst index from 0.901 to 1.5 kPa.m2/g. The effects of dependent variables on the mechanical properties of molded pulp were studied by statistical modelling using a polynomial second order. The empirical models were deduced to satisfactorily fit experimental data with the values of independent variables and allow to quantifiying the effects of each variables. The most influential factor on tensile and burst index of molded pulp was temperature of processing. Whereas, the processing pressure has greater influence on tear index of molded pulp.Keywords:material characterization; binderless, molded pulp; mechanical properties; statistical modelling.